Predictors of Successful Discontinuation of Supplemental Oxygen in Very Low-Birth-Weight Infants with Bronchopulmonary Dysplasia Approaching Neonatal Intensive Care Unit Discharge - Trzaski, Jennifer M.; Hagadorn, James I.; Hussain, Naveed; Schwenn, Janet; Wittenzellner, Claudia (American Journal of Perinatology, 2012)
We sought to identify factors associated with readiness to discontinue supplemental oxygen and to gain weight in very low-birth-weight (VLBW) infants with bronchopulmonary dysplasia (BPD) approaching neonatal intensive care unit (NICU) discharge. From 2004 to 2009, VLBW infants ≥34 weeks’ postmenstrual age (PMA) on nasal cannula supplemental oxygen were challenged with room air at rest, during activity, and feeding as routine care. Outcome and clinical data were collected retrospectively. Challenges were divided into derivation and validation cohorts. We performed comparative and hierarchical logistic regression analyses, constructing a predictive model with passed challenge as outcome. Of 233 infants (birth weight 901 ± 245 g, gestational age 266/ 7 ± 2 weeks), 988 had challenges at 382/ 7 ± 3 weeks’ PMA. Weight gain was 12.4 ± 5 g/kg/d in the week following passed challenges and 11.2 ± 5.3 g/kg/d following failed challenges (p = 0.08). Increasing weight at time of challenge was associated with increased adjusted odds of passing. Increasing capillary pco2, cannula flow rate, pulmonary acuity score, and history of patent ductus arteriosus (PDA) ligation decreased odds of passing. Receiver operating characteristic curve area was 0.82 in the validation cohort. The model performed well within pco2 and pulmonary acuity score subgroups. Weight, pco2, cannula flow rate, pulmonary acuity score, and history of PDA ligation identify infants with BPD ready to maintain saturation and gain weight without supplemental oxygen.
Keywords: VLBW infant; bronchopulmonary dysplasia; supplemental oxygen; predictive model